Cross-continental experimental infections reveal distinct defence mechanisms in populations of the three-spined stickleback Gasterosteus aculeatus. Issue 1959 (29th September 2021) - Piecyk, Agnes; Hahn, Megan A.; Roth, Olivia; Dheilly, Nolwenn M.; Heins, David C.; Bell, Michael A.; Kalbe, Martin
Abstract : Epidemiological traits of host–parasite associations depend on the effects of the host, the parasite and their interaction. Parasites evolve mechanisms to infect and exploit their hosts, whereas hosts evolve mechanisms to prevent infection and limit detrimental effects. The reasons why and how these traits differ across populations still remain unclear. Using experimental cross-infection of three-spined stickleback Gasterosteus aculeatus and their species-specific cestode parasites Schistocephalus solidus from Alaskan and European populations, we disentangled host, parasite and interaction effects on epidemiological traits at different geographical scales. We hypothesized that host and parasite main effects would dominate both within and across continents, although interaction effects would show geographical variation of natural selection within and across continents. We found that mechanisms preventing infection (qualitative resistance) occurred only in a combination of hosts and parasites from different continents, while mechanisms limiting parasite burden (quantitative resistance) and reducing detrimental effects of infection (tolerance) were host-population specific. We conclude that evolution favours distinct defence mechanisms on different geographical scales and that it is important to distinguish concepts of qualitative resistance, quantitative resistance and tolerance in studies of macroparasite infections.